Factors Affecting Bankruptcy in Malaysian Listed Companies - Patricia, Zoe; R, Suganthi; R, Devinaga; Yeen Yen, Yuen; ., Shalini (International Journal of Engineering and Technology, 2018)
In a number of studies bankruptcy has been known to bring about the downfall and embarrassment of firms as well as destroying a lot of careers. On the other hand for bankruptcy of corporate institutions, factors such as accounting aspects that include, profitability, leverage as well as liquidity are mainly the core of this issue as mentioned by Boettcher, Cavanagh, and Xu (1). Nowadays corporate governance has been added into the mix. In order to support both affected and smoothly running firms, it is crucial for researchers to investigate all the aspects of the management of the firm as expressed in their annual reports. The methods focused on in this research includes the models such as, multicollinearity, polled least square model and finally the fixed effect model. The annual reports and indexes were used to get values in the measurements. This study found that corporate governance, firm size and profitability were not significant to the bankruptcy of the firm. However, Liquidity and leverage contributed to firm bankruptcy.  In conclusion, this study is generally meant to explore the impact of different factors that probably contributed to bankruptcy among Malaysian firms.
Keywords: Bankruptcy; corporate institutions; corporate Governance; size; profitability; leverage and liquidity